PAN-ISLAMIC COOPERATION AND ANTI-COLONIALISM BETWEEN THE OTTOMAN CALIPHATE AND THE MALAY WORLD - ARSHAD ISLAM; RUQAIA TAHA AL-ALWANI (Hamdard Islamicus)
Human civilization has been profoundly shaped by the ancient oceanic maritime trading connections linking the Mediterranean World and Africa to China, via the Arabian, Indian, and Southeast Asian ports, shaping social and cultural exchanges enriched by numerous cultures, including the religion of Islam. The Malay World has always been at the crossroads of international maritime traffic, developing a common and diverse culture incorporating local and global elements, notably Hindu-Buddhist, Confucian, and Islamic influences, in a long and generally peaceful civilizational paradigm prior to the advent of European colonial exploitation. The active and multidimensional relations between the Ottoman Caliphate and the Muslim rulers of India and Muslim Southeast Asia have been largely forgotten, despite extensive materials available in Ottoman, and local Malay archives. This paper explores Pan-Islamic cooperation between the Ottoman Caliphate and Southeast Asia in the context of anti-colonial resistance, focusing on specific diplomatic relations between the Sublime Porte and the sultanates of Aceh, Riau, and Jambi from the 16th century onwards, analysing the role of Malay Muslims in the Ottoman Caliphate, and the role of the Ottomans in Sumatran resistance to Dutch colonialism. The latter 19th century witnessed increased interactions between the Ottoman Empire and many local sultanates in Southeast Asia, facilitated by the role of Hadramis, Ottoman consuls, the Pan-Islamist press, and pilgrims and clerics. The history of the Pan-Islamic platform offers great scope for developing countries to autonomously assist each other without neo-imperialist agendas, recovering their historical position and dignity as vibrant, compassionate societies.